APLIKASI SMS GATEWAY UNTUK ABSENSI SISWA SMK MENGGUNAKAN SKALA LIKERT DI SMK NEGERI 1 NGULING - Endang Widia Astuti (STMIK YADIKA BANGIL, 2017)
Along with the development of communication technology and information systems, so the more prepared academic information system based on SMS. Chosen communications technology in the form of SMS is due more practical, inexpensive, and efficient way to deliver information. This excess is very beneficial when utilized for education .Short message service (SMS) is a technology that is very much in demand and are used by many people. In addition to its superior in terms of practicality and ease of use, this technology also comes with a rate which is relatively less expensive for the facility of sending a data message or transfer information in a capacity smaller than the voice / telephone Thus the authors will use to program applications based attendance sms gateway. This application will bridge the gap between walimurid with the school. Information System SMS-Based Elementary School was designed using the programming language PHP and Mysql data base. As well as program design using UML and has a function as a conduit of information attendance and activities of students in the school to the parents to be more easily and efficiently via SMS. Parents do not have to bother anymore to come to school only to findactivities and student attendance.Keywords: PHP, Mysql, student attendance, SMS Gateway